2010
DOI: 10.1186/1479-5868-7-62
|View full text |Cite
|
Sign up to set email alerts
|

What's "quickest and easiest?": parental decision making about school trip mode

Abstract: BackgroundThe potential benefits of active school travel (AST) are widely recognized, yet there is consistent evidence of a systematic decline in the use of active modes of transportation to school since the middle part of the 20th century. This study explored parental accounts of the school travel mode choice decision-making process.MethodsThirty-seven parents of children (17 who walked; 20 who were driven) from four elementary schools in Toronto, Canada participated in semi-structured interviews. The schools… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
120
1
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(126 citation statements)
references
References 31 publications
(57 reference statements)
2
120
1
3
Order By: Relevance
“…Research studies have examined correlations between personal, family, social and environmental factors and children's active/independent commuting to and from school, mainly focusing on health and obesity. The main conclusions of these studies are that the likelihood of walking or cycling to school decreases as travel distance increases, but it is also correlated with the safety of routes and family time constraints (Dellinger and Staunton, 2002;Ewing et al, 2004;Faulkner et al, 2010;McDonald and Aalborg, 2009;McMillan, 2006;Mitra et al, 2010;Sjolie and Thuen, 2002;Timperio et al, 2006;Trapp et al, 2011;Yeung et al, 2008;Ziviani et al, 2004). Previous research has also identified parents' concerns about the absence of adult supervision, the age of the child and fears related to children being assaulted by strangers as primary barriers to active commuting to school.…”
Section: School Commutingmentioning
confidence: 99%
See 1 more Smart Citation
“…Research studies have examined correlations between personal, family, social and environmental factors and children's active/independent commuting to and from school, mainly focusing on health and obesity. The main conclusions of these studies are that the likelihood of walking or cycling to school decreases as travel distance increases, but it is also correlated with the safety of routes and family time constraints (Dellinger and Staunton, 2002;Ewing et al, 2004;Faulkner et al, 2010;McDonald and Aalborg, 2009;McMillan, 2006;Mitra et al, 2010;Sjolie and Thuen, 2002;Timperio et al, 2006;Trapp et al, 2011;Yeung et al, 2008;Ziviani et al, 2004). Previous research has also identified parents' concerns about the absence of adult supervision, the age of the child and fears related to children being assaulted by strangers as primary barriers to active commuting to school.…”
Section: School Commutingmentioning
confidence: 99%
“…Boys seem to be more likely to walk and especially to cycle to school (McDonald, 2012;McMillan et al, 2006). An emerging research topic not only concerns the qualitative work on parents' perceptions but also addresses children's perceptions of school travel and the built environment (Faulkner et al, 2010;Fusco et al, 2012;Line et al, 2010). Children are now considered ''active agents'' who are able to express their own needs about school travel (Fusco et al, 2012).…”
Section: School Commutingmentioning
confidence: 99%
“…En lo que respecta al acceso a los servicios educativos, buena parte de la literatura se centra en el estudio de los medios de transporte utilizados, y en la conveniencia de favorecer el transporte no motorizado como una forma de desarrollar hábitos saludables en los escolares (FAULKNER et al, 2010;MCDONALD et al, 2014). En ese sentido se ha estudiado los obstáculos que para la accesibilidad a la educación pueden imponer las distintas características del entorno, especialmente la existencia de carreteras y tráfico pesado en las inmediaciones de los planteles o las largas distancias existentes (BEJLERI et al, 2011;FITZPATRICK et al, 2012).…”
Section: La Accesibilidad a Los Principales Servicios Urbanosunclassified
“…Previous literature has shown that parent-perceived convenience is an important correlate of travel mode choices McDonald & Aalborg, 2009;McMillan, 2007;Panter et al, 2010a). For instance, Faulkner et al (2010) concluded that once parents have decided whether their child needs to be escorted to/from school, they choose the travel mode that they consider the quickest and most convenient.…”
Section: Social Environmentmentioning
confidence: 99%